Evaluating knowledge and attitudes scales for the care of older adults among nursing students in Ghana - Diana Abudu-Birresborn; Sarah Brennenstuhl; Martine Puts; Lynn McCleary; Vida Yakong; Charlene H. Chu; Lisa Cranley (BMC, 2023)
Abstract Background Understanding nursing students' knowledge about and attitudes toward older adults' using context-specific survey instruments can help to identify and design effective learning and teaching materials to improve the care for persons 60 years and above. However, there are no validated instruments to examine nursing students' knowledge and attitudes toward the care for older adults in the African context. The study aimed to evaluate the items on the Knowledge about Older Patients Quiz and Kogan's Attitudes towards Old People Scale suitable for the African context. Methods A cross-sectional study was conducted using second-and third-year nursing students from two public Nursing Training Institutions in Ghana. Using Sahin's rule of sample size estimate of at least 150 participants for unidimensional dichotomous scales, 170 nursing students were recruited to participate after an information session in their classrooms. Data were collected from December 2019-March 2020 using the Knowledge about Older Patients Quiz and Kogan's Attitudes Towards Old People Scale. Item response theory was employed to evaluate the Knowledge about Older Patients Quiz difficulty level and discrimination indices. Corrected item-to-total correlation analysis was conducted for Kogan's Attitudes towards Old People Scale. The internal consistency for both scales was examined. Results Of the 170 participants, 169 returned completed surveys. The mean age of participants was 21 years (SD = 3.7), and (54%) were female. Of the 30-items of the Knowledge about Older Patients Quiz, seven items were very difficult for most students to choose the correct response, and one was easy, as most of the students chose the correct response. Although 22 items demonstrated appropriate difficulty level, discrimination indices were used to select the final 15- items that discriminated moderately between upper and lower 25% performing students. The Kuder-Richardson-20 reliability was. 0.30, which was low. Considering Kogan's Attitudes towards Old People scale, 10-items were removed following negative and low corrected item-to-total correlation and a high Alpha coefficient if items were deleted. The final 22-items had a Cronbach alpha coefficient of 0.65, which was moderately satisfactory. Conclusion Evaluation of the scales demonstrated essential content validity and moderate internal consistency for the context of our study. Further research should focus on ongoing context-specific refinement of the survey instruments to measure nursing students' knowledge about and attitudes toward caring for older adults in the African context.